Tinjauan Filosofis Aspek Kepastian Hukum Antara Pemerintah Dengan Pemerintah Daerah Dalam Implementasi Undang-Undang Penanaman Modal Di indonesia - Ramlan ' (Fakultas Hukum Universitas Riau, 2012)
State duty to promote the general welfare of its people. For that, one of the policies pursued by the Government is giving authority to local governments to implement and execute development activities as well as greater authority in obtaining sources of financing, by way of delegated authority on local government investments. Due to matters concerning local government in the field of investment only on the criteria of externality, accountability, and efficiency, what is meant by these criteria are not clear in its elaboration.